Case Study on Migrated Women Employment from Rural to Urban Areas in Uttarakhand - Verma , Tulika Uniyal (Gyan Management Journal, 2023)
This case study explores the phenomenon of women’s migration from  rural to urban areas in Uttarakhand, India, and its impact on their  employment patterns. Uttarakhand, a hilly state located in northern  India, has witnessed significant rural-to-urban migration in recent  years. The study investigates the socio-economic factors driving this  migration, the challenges faced by migrant women in the process,  and the opportunities and constraints they encounter in securing  employment in urban settings. The research employs a mixed methods approach, combining qualitative interviews and focus group  discussions with quantitative analysis of secondary data. Primary data  collection involves interviews with migrated women, community  leaders, and key stakeholders in urban areas, along with focus groups  comprising both migrants and non-migrants. Secondary data sources  include government reports, academic studies, and relevant literature.  The findings reveal several key insights. Firstly, economic factors, such  as lack of employment opportunities, limited agricultural productivity,  and aspirations for better livelihoods, emerge as primary motivations  for rural women’s migration to urban areas. Secondly, social factors,  including changing gender roles, education, and social networks,  play a significant role in the decision-making process. However, the  study also uncovers numerous challenges faced by migrated women,  including discrimination, exploitation, inadequate access to education  and healthcare, and limited social support networks. Moreover, the
Keywords: Migrated women employment; Rural to urban migration; Gender-inclusive development,; Sustainable livelihoods